The effectiveness of office spatial application on Perumda employee performance Tirta Lestari Drinking Water, Tuban Regency / Lydia Apriliani, Amaliyah and Moh. Ibnu Sina - Apriliani, Lydia; Amaliyah, Amaliyah; Moh. Ibnu Sina, Moh. Ibnu Sina (Universiti Teknologi MARA, Cawangan Melaka, 2022)
The main facilities and infrastructure in an economic activity are offices. Spatial arrangement in office activities is one of the needs that must be considered by the company. In the preparation of this final task the research method used is descriptive qualitative with data collection techniques through interview results, direct religion, and documentation. The application of spatial planning in Perumda Air Minum Tirta Lestari Tuban Regency is an open office layout with a model of working table arrangement in the form of class and L. Conclusions that can be taken are most of the principles of spatial layout has been applied and the influence of the work environment on the performance of employees has met the needs of employees, but still needed improvements in terms of maintaining the cleanliness and neatness of the employee's work desk , the addition of a special archive room, procurement of bulkheads, making the room soundproof, limiting and adjusting the number of employees to the capacity of the room.